Agency costs and credit availability: an international study. Issue 3 (18th June 2021) - Bahlous-Boldi, Mejda
Abstract : Purpose: This paper aims to investigate the link between agency costs mitigation via three levels of rights protection (minority rights protection, enforcing contracts, resolving insolvency issues) provides the propitious climate for financing investment opportunities around the world. Design/methodology/approach: We use Bartlett's three-group method to stratify countries based on how well they protect investors as measured by the scores provided in the Doing Business dataset developed by the world bank for 189 countries. We then test a variety of independent hypotheses that the alleviation of agency costs via three levels of protection (minority investors' rights, contract enforcement, resolving insolvency issues) is associated with better access to credit via the banking system, better valuation of listed firms via the stock market and higher investment and growth. Findings: Our findings support Agency Theory which explains why the absence of legal protection of external investors leads to stock markets and financial institutions failing to fulfill their role of financing the economy. Practical implications: The policy implication from this study indicates that countries ought to (1) develop legislation that protects investors' rights, (2) improve the quality of their judicial system in terms of enforcing the legislation and (3) build the framework for resolving disputes during insolvency as these are important ingredients for a developed financial system. Originality/value: We use the World bank dataset and a new methodology to quantify the significance of the relationship between minority rights protection, ineffective enforcement, lack of bankruptcy laws and access to firm financing via the banking sector and the stock market. It provides new evidence that the quality of the judicial system in a country matter for firms' ability to raise financing and enhance value creation. Abstract : 研究目的: 本文旨在探討一個假設，該假設為透過三級別權利保障（保障少數群體的權利、執行合同、解決破產問題）的代理成本緩減會為世界各地的金融性投資機會提供良好的氣侯。 研究設計/方法/理念: 我們以巴特利特（Bartlett）的三組法把國家分組，分組方法是基於該國家保障投資者的程度，而保障程度是以世界銀行為189個國家而制定的營商資料集內提供的評分來衡量的。我們把國家分組後，便就各樣的獨立假設進行測試。這些假設是：透過三級別保障（保障少數股權投資者的權利、合同的執行、解決破產問題）的代理成本緩減是連繫於透過銀行系統而產生的更佳信貸途徑，透過股市的更佳上市公司估值及更高的投資和增長。 研究結果: 研究結果証實了代理理論，該理論說明為何當外來投資者沒有得到法律保障時，結果會導致股票市場和金融機構不能履行其為經濟提供資金的角色。 實際的意義: 本研究具有政策方面的意義，因研究顯示了國家應該：（1）設立保障投資者權利的法律；（2）在執行法律方面，改善其司法系統的素質；（3）建立解決破產時爭議的體系。這些是應該做的，因它們是一個已發展的金融體制的重要元素。 研究的原創性/價值: 本文強調了一個保障投資者權利的法律環境所需的三個特定要素：對少數股權投資者權利的保障、有效的執行、有效的破產法律及透過銀行部門和股票市場而取得公司融資。這提供新的證據, 證實這三級別權利保障對公司籌集資金及提高價值創造的能力而言至為重要。